Does types of atrial fibrillation matter in the impairment of global and regional left ventricular mechanics and intra-ventricular dyssynchrony? - Zhen, Xiao-Wen; Li, Wen-Cai; Wang, Hua; Song, Nian-Peng; Zhong, Lin (Frontiers in Cardiovascular Medicine, 2022)
Background: Atrial fibrillation (AF) is the most common sustained cardiac arrhythmia, which is associated with cardiac dysfunction. This study aimed to compare the impairment severity of left ventricular strain and intra-ventricular dyssynchrony using echocardiography-derived velocity vector imaging in patients with different types of AF without heart failure. Methods: 168 nonvalvular AF patients with normal left ventricular ejection fraction (98 paroxysmal AF patients and 70 persistent AF patients) and 86 healthy control subjects were included in this study. Regional and global left ventricular longitudinal and circumferential strain were measured. Time to regional peak longitudinal strain was measured and the standard deviation of all 12 segments (SDT-S) was used as a measure of intra-ventricular dyssynchrony. Results： Significantly lower GLS (-18.71±3.00% in controls vs. -17.10±3.01% in paroxysmal AF vs. -12.23±3.25% in persistent AF, P<0.05) and GCS (-28.75±6.34% in controls vs. -24.43±6.86% in paroxysmal AF vs. -18.46±6.42% in persistent AF, P<0.01) were observed in either persistent AF subjects or paroxysmal AF subjects compared with healthy control subjects (P <0.05). The impairment was much worse in persistent AF subjects compared with paroxysmal AF subjects (P<0.001). Intraventricular dyssynchrony was found in both persistent AF patients and paroxysmal AF patients, and it’s worse in persistent AF patients (52±18ms in controls, 61±17ms in paroxysmal AF, and 70±28ms in persistent AF, P<0.05). Multivariate regression analysis revealed AF types were independent risk factors of GLS, GCS, and intraventricular dyssynchrony. Conclusions: AF types were not only associated with impaired longitudinal and circumferential left ventricle mechanics but also intra-ventricular mechanical dyssynchrony. Worse systolic mechanics and intra-ventricular dyssynchrony were found in patients with persistent AF compared with these in patients with paroxysmal AF.